A Price Theory of Multi-Sided Platforms - Weyl, E. Glen (American Economic Review, 2010)
I develop a general theory of monopoly pricing of networks. Platforms use insulating tariffs to avoid coordination failure, implementing any desired allocation. Profit maximization distorts in the spirit of A. Michael Spence (1975) by internalizing only network externalities to marginal users. Thus the empirical and prescriptive content of the popular Jean-Charles Rochet and Jean Tirole (2006) model of two-sided markets turns on the nature of user heterogeneity. I propose a more plausible, yet equally tractable, model of heterogeneity in which users differ in their income or scale. My approach provides a general measure of market power and helps predict the effects of price regulation and mergers. (JEL D42, D85, L14)